Onlay Versus Sublay Technique of Repairing Ventral Abdominal Hernia - Qasim Ali. Faisal Murad, Tahir Ashraf Awan, Atif Khan, Asif Zafar Malik (Journal of Rawalpindi Medical College, 2013)
Background: To compare Onlay versus Sublay technique of repairing ventral abdominal hernia Methods: In this compatrative study patients of ventral abdominal hernia (n=150) were included. Seventy six were in onlay group (Group A) and 74 in sublay group (Group B). In group A patients (onlay) the hernial sac was not opened unless the contents were irreducible. In such conditions the sac was opened and the contents were dissected and reduced, sac was closed, inverted and sutured with vicryl 2/0. An onlay polypropylene mesh was inserted. In Group B(sublay) midline laprotomy incision was given and in cases of incisional hernias excision of the previous scar. Afterwards hernial sac was opened. After adhenolysis the bowels were covered with a towel to avoid any iatrogenic injury to the bowel. A sufficient mesh overlap with a subduction of healthy tissue of at least 6 cm in each direction was provided to avoid recurrence at the edges due to shrinkage of prosthesis. After preparation of the mesh bearing the peritoneal layer was closed with an absorbable running suture. The mesh was then placed into contact with the muscle fibres. Follow up in each group was done for the period of one month with the interval of 7days, 15 days and 30days. Results: The mean operative time in group A was 49.35 ± 8.29 minutes and in group B 63.15 ± 15.0 minutes (p< 0.001). The patients with seroma in group A were 12 percent, 34.67percent and 0 percent on 7th , 15th and 30th day respectively .Superficial surgical site (SSI) in the same group was 17.33 percent , 6.67 percent and 0 percent in 7th, 15th and 30th day respectively. The patients who presented with seroma in group B were 6.3percent, 3.78percent and 0 percent on 7th , 15th and 30th day respectively .SSI in the same group B were 4.3percent , 2.9 percent and 0 percent on 7th, 15th and 30th day respectively. Conclusion: Sublay is better than onlay technique with less postoperative complications, but operative time is slightly greater in sublay technique.